2020
DOI: 10.1002/ijc.33016
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor light at night and postmenopausal breast cancer risk in the NIH‐AARP diet and health study

Abstract: Circadian disruption may play a role in breast carcinogenesis. Previous studies reported relationships between outdoor light at night (LAN) and the breast cancer risk, but their findings are mixed. There is also a need to examine LAN and breast cancer incidence according to different individual and environmental characteristics to identify subpopulations at greater risk associated with LAN exposure. We studied residential outdoor LAN estimated from satellite imagery at baseline (1996) in relation to postmenopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
2
36
0
1
Order By: Relevance
“…Multiple studies have reported an association between LAN and higher risks for various chronic diseases, including cancer 29 . For example, artificial outdoor LAN assessed by satellite imagery has been linked to an increased risk of breast cancer in several large cohorts of middle‐aged to older women, including the NIH‐AARP Diet and Health Study 30,35,41 . Specifically, these studies reported that compared with women living in the lowest quintile of LAN, those in the highest quintile had an 11% to 14% increase in breast cancer risk, and the association appeared to be stronger for estrogen receptor (ER)–positive breast cancer 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have reported an association between LAN and higher risks for various chronic diseases, including cancer 29 . For example, artificial outdoor LAN assessed by satellite imagery has been linked to an increased risk of breast cancer in several large cohorts of middle‐aged to older women, including the NIH‐AARP Diet and Health Study 30,35,41 . Specifically, these studies reported that compared with women living in the lowest quintile of LAN, those in the highest quintile had an 11% to 14% increase in breast cancer risk, and the association appeared to be stronger for estrogen receptor (ER)–positive breast cancer 30 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, artificial outdoor LAN assessed by satellite imagery has been linked to an increased risk of breast cancer in several large cohorts of middle‐aged to older women, including the NIH‐AARP Diet and Health Study 30,35,41 . Specifically, these studies reported that compared with women living in the lowest quintile of LAN, those in the highest quintile had an 11% to 14% increase in breast cancer risk, and the association appeared to be stronger for estrogen receptor (ER)–positive breast cancer 30 . It has been suggested that exposure to LAN reduces nighttime production of melatonin, which acts as a tumor suppressor partially through its anti‐estrogenic actions 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings corroborate the previously reported positive association between LAN and breast cancer risk and extend prior work by characterizing this relationship among both Blacks and Whites in a large cohort of women recruited from disadvantaged communities. Several previous cohort investigations, including in the California Teachers Study, 4 the Nurses’ Health Study II, 5 and the National Institutes of Health–AARP Diet and Health Study, 6 reported a modest increase in breast cancer risk associated with higher outdoor LAN levels (10–14%, comparing the highest to the lowest quintile). In our SCCS analysis, the effect sizes appeared larger compared with those in previous cohorts 4 , 5 , 6 although the distribution of LAN was similar and the confidence intervals overlap.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 Several epidemiologic studies have linked higher outdoor LAN estimated from satellite imagery to elevated incidence of breast cancer, including in cohorts predominantly comprised of White women with relatively high socioeconomic status (SES). 4 , 5 , 6 However, it remains unclear whether LAN is associated with breast cancer risk among Black women and women of lower SES.…”
Section: Introductionmentioning
confidence: 99%